A benchmark for oncologic outcomes and model for lethal recurrence risk after transoral robotic resection of HPV-related oropharyngeal cancers. (April 2022) - Brody, Robert M.; Shimunov, David; Cohen, Roger B.; Lin, Alexander; Lukens, John N.; Hartner, Lee; Aggarwal, Charu; Duvvuri, Umamaheswar; Montone, Kathleen T.; Jalaly, Jalal B.; LiVolsi, Virginia A.; Carey, Ryan M.; et al.
Graphical abstract: Highlights: High curative salvage rates for locoregional recurrences contribute to excellent long-term oncologic outcomes after TORS-based therapy for HPV+ oropharyngeal cancers. Distant recurrences cause most of the disease-specific mortality for these patients. Positive surgical margins from TORS indicate risk of distant recurrence even if locoregional control is achieved. Abstract: Objectives: Increasing use of transoral robotic surgery (TORS) is likely to impact outcomes for HPV+ oropharyngeal squamous cell carcinomas (OPSCCs). We aimed to describe oncologic outcomes for a large HPV+ OPSCC cohort after TORS and develop a risk prediction model for recurrence under this treatment paradigm. Materials and methods: 634 HPV+ OPSCC patients receiving TORS-based therapy at a single institution were reviewed retrospectively to describe survival across the entire cohort and for patients suffering recurrence. Risks for distant metastatic recurrence (DMR) and locoregional recurrence (LRR) were modeled using multivariate logistic regression analyses of case-control sub-cohorts. Results: 5-year overall and recurrence-free survival were 91.2% and 86.1%, respectively. 5-year overall survival was 52.5% following DMR and 83.3% after isolated LRR (P = .01). In case-control analyses, positive surgical margins were associated with DMR (adjusted OR 5.8, CI 2.1–16.0, P = .001), but not isolated LRR, and increased DMR risk 4.2 fold in patients with early clinical stage disease. By contrast, LRR was associated with not receiving recommended adjuvant therapy (OR 13.4, CI 6.3–28.5, P < .001). Conclusions: This study sets a benchmark for oncologic outcomes from HPV+ OPSCC after TORS-based therapy. Under this treatment paradigm, margins are relevant for assessing lethal recurrence risk during clinical trial design and post-treatment surveillance.